Decompressive craniectomy in trauma: What you need to know - Solomou, Georgios; Sunny, Jesvin; Mohan, Midhun; Hossain, Iftakher; Kolias, Angelos G; Hutchinson, Peter J (United States, 2026)
Decompressive craniectomy (DC) is a surgical procedure in which a large section of the skull is removed, and the underlying dura mater is opened widely. After evacuating a traumatic acute subdural hematoma, a primary DC is typically performed if the brain is bulging or if brain swelling is expected over the next several days. However, a recent randomized trial found similar 12-month outcomes when primary DC was compared with craniotomy for acute subdural hematoma. Secondary removal of the bone flap was performed in 9% of the craniotomy group, but more wound complications occurred in the craniectomy group. Two further multicenter trials found that, whereas early neuroprotective bifrontal DC for mild to moderate intracranial hypertension is not superior to medical management, DC as a last-tier therapy for refractory intracranial hypertension leads to reduced mortality. Patients undergoing secondary last-tier DC are more likely to improve over time than those in the standard medical management group. The overall conclusion from the most up-to-date evidence is that secondary DC has a role in the management of intracranial hypertension following traumatic brain injury but is not a panacea. Therefore, the decision to offer this operation should be made on a case-by-case basis. Following DC, cranioplasty is warranted but not always feasible, especially in low- and middle-income countries. Consequently, a decompressive craniotomy, where the bone flap is allowed to "hinge" or "float," is sometimes used. Decompressive craniotomy is also an option in a subgroup of traumatic brain injury patients undergoing primary surgical evacuation when the brain is neither bulging nor relaxed. However, a high-quality randomized controlled trial is needed to delineate the specific indications and the type of decompressive craniotomy in appropriate patients.